Research of geomagnetically conjugate phenomena in Antarctica since the IGY - Nagata, Takesi (1987)
P(論文) The geomagnetically conjugate relationship studies of the magnetospheric phenomena between the southern auroral zone in Antarctica and the northern auroral zone over Europe and America are historically reviewed, starting with the IGY (1957-1958) results and then summarizing key results obtained by the international cooperative research programs such as the IGC (1959), the IQSY (1964-1965), the IASY (1967-1971) and the IMS (1976-1979). The observed conjugate magnetospheric phenomena are divided into the following three topics according to the physical guiding processes for their conjugacy characteristics. (I) The auroral particle precipitation by the field-line guidance, resulting in the visual auroras, the auroral X-rays, the cosmic noise absorption (CNA) by the ionosphere and the polar magnetic substorms. (II) The field-aligned propagation of the whistler-mode plasma waves, which cover the ELF and VLF magnetospheric plasma waves that are often bouncing along the field lines between the conjugate ionospheric areas. (III) The hydromagnetic resonance system of the earth's magnetosphere, which covers most parts of the conjugate characteristics of the Pc 3-5 hydromagnetic waves. The Pc 1 pulsations are summarized under topic (III), though their wave characteristics are more similar to the whistler-mode waves under topic (II). departmental bulletin paper